THE EFFECT OF EMOTIONAL INTELLIGENCE, SELF-EFFICIENCY ON LEARNING ACHIEVEMENT WITH LEARNING BEHAVIOR AS MODERATING VARIABLES - Ismawati, Ayu Fitria; Setyawati, Sri Murni; Martini, Sri (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
This study aim to the effect of emotional intelligence, self efficacy, on economic learning achievement, and learning behavior as moderating variables. This study uses quantitative research with survey method. he population in this study were 151 students using the proportional random sampling method and produced 110 samples. Methods of data collection using the methods of documentation, questionnaire analysis tools used multiple regression analysis, moderated regression analysis. The results of this study are emotional intelligence has a positive effect on economic learning achievement of students in class X IPS MAN 1 Banyumas, self-efficacy has a positive effect on economic learning achievement of students in class X IPS MAN 1 Banyumas, learning behavior does not moderate the influence of emotional intelligence on economic learning achievement of students in class X IPS MAN 1 Banyumas, learning behavior does not moderate the effect of self-efficacy on economic learning achievement of students in class X IPS MAN 1 Banyumas, learning behavior has a positive effect on economic learning achievement of students in class X IPS MAN 1 Banyumas. The implication given is that teachers should optimize emotional intelligence, increase student self-efficacy, and foster good behavior, further researchers can add other variables that have not been studied.